Original articleMaintenance of the rat transgenic model of familial amyotrophic lateral sclerosis expressing human SOD1G93A mutation - Herbik, Magdalena A.; Chrapusta, Stanisław J.; Kowalczyk, Anna; Grieb, Paweł (Folia Neuropathologica, 2006)
A colony of transgenic rats expressing the human mutant Cu,Zn superoxide dismutase gene (hSOD1 G93A ) that is associated with some cases of familial form of amyotrophic lateral sclerosis (ALS) has been maintained in the Animal House of the Polish Academy of Sciences Medical Research Centre since 2003. This transgenic model, generated by Howland et al. (Proc Natl Acad Sci USA 2002; 99: 1604-1609), has been obtained under the material transfer agreement from Wyeth Corporation. The transgenic SOD1 G93A (or ‘Howland’) rats develop neurological and neuropathological symptoms reminiscent of human ALS, i.e. progressive loss of motoneurons leading to paralysis and death. This paper describes maintenance of the transgenic rat colony, and general procedures used in experiments with these animals (i.e. genotyping, neurological observations, anaesthesia, etc.). At the beginning of the colony, up to the 3rd generation of the rats, symptoms of the model disease appeared at 95-125 days of age, and the animals survived till 120-145 days of age. Thereafter a gradual change in the disease phenotype occurred, and in the 8th generation approximately 1/3 of the rats displayed much slowed disease progression.